Synthesis and Characterization of Some Complexes of Manganese(II), Iron(II) and Cobalt(II) With Decylxanthate and Their Adducts With Nitrogen Base Ligands - Mahameed Ameen Al-Badrane; Fadia J Ahmed (College of Education for Pure Sciences, 2023)
This research includes the synthesis and characterization of twelve new complexes of mono nuclear xanthate for a number of transition metal ions Mn(II) , Fe(II) , Co(II) and through the interaction with ligand (decyl xanthate potassium) and complexes of formula [M(DEXANT)2] were formed , as : M= Mn(II) , Fe(II) , Co(II) and then the interaction of these complexes with Lewis bivalve bases , to give complexes with the formula [M(DEXANT)2 . L], where : L= 1,10-phenanthroline , 8-hydroxyquinoline, 2,2-Pipyridine. The prepared complexes were characterized by melting point , atomic absorption, micro elemental analysis , infrared , nuclear magnetic resonance spectrum of the proton , molar electrical conductivity , electronic absorption spectra and susceptibility measurements. Magnetic moment and electronic spectra indicated that the complexes of type [M(DEXANT)2] had a tetrahedral geometry, while complexes of type [M(DEXANT)2.L] had an octahedral geometry,The conductivity measurements proved the non-electrolytic behavior of all compounds .